Parallel-Pipelined-Memory (P2m) Of Blowfish Fpga-Based Radio System With Improved Power-Throughput For Secure Zigbee Transmission - Ahmad, Rafidah (2020)
Currently, the advanced encryption standard (AES) scheme is employed by most of the Institute of Electrical and Electronic Engineers (IEEE) standards to secure the data transmission of mobile devices specifically in internet of things (IoT) network. However, this scheme requires high compute platform and memory to support the encryption or decryption process which may not exist in all IoT-attached devices. In order to overcome this issue, this research work proposed an alternative cryptography scheme with improved power-throughput and reduced hardware utilization to be considered as a replacement to the existing AES. Based on the performance analysis among the symmetric cryptography schemes, the AES-128 and Blowfish schemes have been chosen to be enhanced and developed based on Zynq- 7000 field programmable gate array (FPGA) technology by using three design techniques comprised of parallel, pipelined and memory (P2M) techniques. At software level, the findings showed that the proposed Blowfish design had better performance with slices occupied and power consumption decreased by 45.3% and 94% respectively, and double throughput value was generated if compared to the proposed AES-128 design. Despite of these, the proposed AES-128 design increased the throughput by 22% and reduced the power consumed to 56% with 46.8% slices usage compared to the AES designs from previous studies. At hardware level, the proposed Blowfish design continued to be implemented and validated on ZedBoard and Zynq7000 AP SoC ZC702 FPGA platforms operated at 2.4 GHz ZigBee standard via XBee-PRO ZigBee through-hole XBP24CZ7PIT-004 for real-time data transmission. Two FPGA-based radio platforms were used as transmitter and receiver to form a two-way communication and measured in non-line-of-sight (NLOS) indoor environment based on point-to-point (P2P) topology within wireless personal area network (WPAN). The performance results indicated that the proposed P2M Blowfish radio system possessed a good quality in wireless data transmission with the bit-error-rate (BER) of 6.25x10-3, maximum signal strength of -34.58 dBm and maximum communication range of 61 m at 10 dBm transmitter radio frequency (RF) power level. The improvement in performance analysis either in the software or hardware level shown by the proposed P2M Blowfish has confirmed that this design has the ability to replace the existing AES scheme in mobile devices for the IoT application.